The Role of Electronic Word of Mouth (E-WOM) on Purchase Decisions for Skin Care Products - Ida Farida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The companies in the current era of globalization are aggressively competing to gain a large market share in the beauty industry, because the beauty industry is a business that has quite a lot of enthusiasts, especially for women and includes consumables. The trend of using sosial media as a disseminator of information has increased. Because Indonesian people are very active in using sosial media. The media used in terms of disseminating information through the well-known electronic word of mouth is sosial media. The purpose of this study was to determine the role of electronic word of mouth (E-WOM) on purchasing decisions of skin care products. The qualitative method used in this study used descriptive qualitative data analysis techniques, by conducting observations, interviews and documentation of five informants who came from IAIN Bone campus students. Based on the results of the study, the authors found that electronic word of mouth (E-WOM) plays an important role in purchasing decisions for skin care products. This shows that the more positive and negative reviews from sosial media users, the greater the influence on purchasing decisions for skin care products.